Utilization of ICU Rehabilitation Services in Pediatric Patients With a Prolonged ICU Stay*. Issue 9 (September 2021) - Betters, Kristina A.; Le, Truc M.; Gong, Wu; Lindsell, Chris J.; Smith, Heidi AB; Smith, Andrew H.
Abstract : OBJECTIVES: To describe rehabilitation practice patterns among critically ill children with prolonged ICU stays and explore the association between institution-level utilization of rehabilitative services and patient outcomes. DESIGN: Retrospective cohort study using an administrative database of inpatient clinical and resource utilization data from participating pediatric hospitals in the United States. Center-level utilization of physical therapy and occupational therapy among critically ill patients was used to divide hospitals by quartile into high utilization centers or standard utilization centers. SETTING: Fifty-one pediatric hospitals in the United States. PATIENTS: Critically ill pediatric patients with prolonged critical illness (defined as an ICU length of stay of at least 7 d) discharged from July 2016 to June 2017. INTERVENTIONS: Not applicable. MEASUREMENTS AND MAIN RESULTS: Seventeen thousand four hundred seventy encounters met criteria for study inclusion. Of those, 6, 040 (35%) were not charged for either physical therapy or occupational therapy services. There was wide variability in center-level utilization of rehabilitative services while in the ICU, ranging from 81% utilization of physical therapy or occupational therapy services among high utilization centers to 46% utilization among centers within the lowest quartile. In univariate analyses, children cared for at an high utilization center were less likely to require discharge to an inpatient rehabilitation facility (1.7% vs 3.5%; p < 0.001) and less likely to incur a new pressure injury (2.2% vs 3.1%; p = 0.001). In multivariable analyses, the direction and magnitude of effects remained similar, although the effect was no longer statistically significant (discharge to inpatient rehabilitation facility: odds ratio, 0.64; 95% CI, 0.18–2.26; pressure injury: odds ratio, 0.77; 95% CI, 0.48–1.24). CONCLUSIONS: Institutional use of rehabilitative services for children with prolonged critical illness varies greatly in the United States. Further research is needed into the potential benefits for patients cared for at centers with high usage of rehabilitation services in the ICU during prolonged critical illness.